Preferential enhancement of older human T cell cytokine generation, chemotaxis, proliferation and survival by lenalidomide - Huang, Mei-Chuan (Clinical immunology (Orlando, Fla.), 2011)
Copyright © 2010 Elsevier Inc. All rights reserved.